The favoured child - Gregory, P., ....- (London : HarperCollins Publishers, 2001)
The second novel in the bestselling Wideacre Trilogy, a compulsive drama set in the eighteenth century. By Philippa Gregory, the author of The Other Boleyn Girl and The Virgin’s Lover. The Wideacre estate is bankrupt, the villagers are living in poverty and Wideacre Hall is a smoke-blackened ruin. But in the Dower House two children are being raised in protected innocence. Equal claimants to the inheritance of Wideacre, rivals for the love of the village, they are tied by a secret childhood betrothal but forbidden to marry. Only one can be the favoured child. Only one can inherit the magical understanding between the land and the Lacey family that can make the Sussex village grow green again. Only one can be Beatrice Lacey’s true heir.
Keywords: Fiction